Breastfeeding Self Efficacy Among Pregnant Women - Ummah, Faizatul; Rosida, Luluk (Sean Institute, 2022)
The provision of breast milk to infants is proven to have many benefits for the health of mothers and babies, but the coverage of exclusive breastfeeding at the global and national levels is still low. Breastfeeding self-efficacy is an important factor that greatly influences the exclusivity and duration of breastfeeding for infants. The level of self-efficacy of breastfeeding can be influenced by the socio-demographic conditions of the mother. This study aims to determine the relationship between age, education, occupation and parity with breastfeeding self-efficacy in pregnant women. Analytical research method Cross sectional. The sample of the study was 30 people in the final trimester of pregnancy by purposive sampling. The independent variable data collection (age and parity) used a closed questionnaire and the dependent variable (breastfeeding self-efficacy level) was measured using a BSES questionnaire with a Likert scale. Bivariate data analysis using Chi-square test. Almost all (90%) pregnant women are of healthy reproductive age, more than some (53.33%) are primigravida, most (66.67%) have secondary education, more than some (60%) do not work, and some (50%) ) had a low level of breastfeeding self-efficacy. The results of statistical tests showed that there was an effect of parity with breastfeeding self-efficacy in pregnant women (p=<0.01), while age, education and occupation did not affect breastfeeding self-efficacy (p>0.05). It is recommended for health workers to pay more attention to and improve breastfeeding education for primigravida who do not have breastfeeding experience so that they have high breastfeeding self-efficacy.